Implicit ideologies in discourse representation of Malaysian English newspapers - Tharmalingam, Selvarajah (2013)
Language policy decisions in multi-ethnic Malaysia never fail to attract contestations. Several major language policy decisions in recent times have rocked the nation’s education system to the core. The government’s latest decision to abolish the policy “English for teaching Mathematics and Science” after a run of nine years (ETeMS) and in its place implementing a new policy “To Uphold Bahasa Malaysia and to Strengthen the English Language” (the Malay acronym being MBMMBI) has triggered much dissatisfaction. The new policy advocates the use of Malay language to teach Mathematics and Science in the national schools. This policy, implemented hastily in 2011, faced the wrath of the people as neither the parents nor the students could adapt or react to the sudden change. Even the academics were caught off-guard especially when public examinations results statistics show that the students improved remarkably in English language during the era of EteMS. The public felt that it is not a right move to change a winning formula overnight. On the other hand, the newspapers were publishing reports favouring the MBMMBI policy. The question that arises is whether or not news reports reflected the real sentiments of the masses. Were the mainstream papers censoring divergent views on the issue? This appears so as many concerned citizens were resorting to publishing their views in online portals. This research sought to answer the following questions: Why do mainstream newspapers publish only selective reports on the policy decision? Who do the newspapers represent? Are there any implicit ideologies in the discourse representation of the newspapers? The study uses the discourse representation framework advocated by Fairclough (1995). This paper critically examines the tendencies in the discourse representation of newspapers and to explain how these tendencies accommodate ideologies implicit in news production. Keywords: ideology, hegemony, discursive event, discursive practices, discourse representation, primary discourse, secondary discourse, language policy, newspapers